Zagreb Root-Indices of Graphs with Chemical Applications - Niko Tratnik; Petra Žigert Pleteršek (Mathematics)
Root-indices of graphs are mathematical tools that help us to understand complex systems, like molecules and networks, by capturing key structural information. In this study, we introduce two new root-indices, the first and the second Zagreb root-index, and we analyze their properties. We apply these indices to chemical structures like benzenoid molecules and octane isomers, showing that they sometimes provide better insights than traditional indices. We also compare the effectiveness of several root-indices with their standard versions, highlighting their ability to distinguish between different graph structures.